Evaluating the Efficacy of the Learner-Centered Approach (LCA) in English Language Teaching: An Educator's Insight (Bologna Process System as an Example) - Hassan, Shaima Ahmed (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study investigates English language educators' perspectives on the efficacy of The Learner-Centered Approach (LCA) within the context of the Bologna process reforms in European higher education. Despite the growing adoption of LCA, there is limited research on educators' views regarding its impacts on teaching methodologies, classroom dynamics, student engagement, and learning outcomes. To address this gap, a quantitative questionnaire was administered to a purposive sample of 33 English language educators from various European institutions. The questionnaire items were developed based on key LCA principles and strategies. Descriptive and inferential statistical analyses, including one-sample t-tests, independent samples t-tests, and one-way ANOVA, were conducted using SPSS. The findings indicate overall favorable orientations among educators towards the LCA, with a significantly higher mean score than the neutral midpoint. However, no significant differences were found based on educators' gender or teaching experience, suggesting complex dynamics shaping their views that warrant further qualitative exploration. The study contributes empirical insights to inform the implementation of learner-centered policies and pedagogies in English language instruction. Recommendations include tailoring curricula, adopting classroom strategies, establishing feedback mechanisms, and providing institutional support. Future research should employ mixed-methods designs to comprehensively understand educators' perspectives and experiences with LCA in diverse contexts.